Librarian involvement in Research Ethics: An Entry Point into the World of Sponsored Research. - Jessica Adamick (Issues in Science and Technology Librarianship, 2011)
This article deals with the increasing involvement of libraries and librarians with sponsored research. It discusses the attendant ethical aspects of this increasing involvement in the areas of consulting with principal investigators during proposal development or providing workshops on data management best practices. It emphasizes the necessary for librarians to have training in ethics in response to the training requirement of the U.S. National Science Foundation (NSF).